The corpses in the Guandu River: considerations on the formation of a social imaginary in the third quarter of the 20th century (Tempo e Argumento, 2023)
This article situates and problematizes the social imaginary that links the Guandu River, in the Baixada Fluminense, to extermination practices. Several press vehicles from Rio de Janeiro reaffirm the common use of this river as a disposal point for human corpses, allowing the construction and perenization of a social imaginary expressed in several brazilian cultural goods, such as poetry, police chronicles, cinema, plastic arts and music. Aiming to comprehend the historical formation of this imaginary, a survey of editions from three Rio de Janeiro’s newspapers from the third quarter of the 20th century was carried out at the Digital Newspaper Library of the Brazilian National Library, compiling the content published with direct references to corpses in the Guandu river. The systematization of the compilled data revealed three regions of interest, between 1961 and 1964, which deserved better attention regarding the possible formation of a social imaginary associating Guandu with killing practices: the case of the “Assault on the paying train”, the “Operation killer of beggars” and the “Vigilantes of Death” case.
Keywords: Guandu river; extermination; social imaginary; press; brazilian culture